Respuesta :

Answer:

 y = 0

Step-by-step explanation:

-3(y-3)=9

One solution was found :

                  y = 0

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    -3*(y-3)-(9)=0

Step by step solution :

Step  1  :

Equation at the end of step  1  :

 (0 -  3 • (y - 3)) -  9  = 0

Step  2  :

Equation at the end of step  2  :

 -3y  = 0

Step  3  :

Solving a Single Variable Equation :

3.1      Solve  :    -3y = 0

Multiply both sides of the equation by (-1) :  3y = 0

Divide both sides of the equation by 3:

                    y = 0

Answer:

No solution

Step-by-step explanation:

–3|y – 3| = 9

⇌       (Divide both sides by -3)

|y – 3| = -3  impossible

because  |y – 3| is greater than 0 and -3 is less than 0.

Otras preguntas